Optimization On Subcritical Fluid Extraction Of Zingiberene - Paramita, Vita; Yulianto, Mohamad Endy; Hartati, Indah; Bahrudin, Udin; Broto, R. T. D. Wisnu (Journal of Vocational Studies on Applied Research, 2019)
The establishment of subcritical fluid application for zingiberene extraction was studied by employing water as a green solvent. The zingiberene content was observed by using Liquid Chromatography-Mass Spectrofotometry and regarding to the independent variable of temperature, extraction time, ginger-solvent ratio and aging time. By applying subcritical water, the critical value of zingiberene content obtained was 0.036%. This value was approached by the surface modeling of alpha for rotatability design which performed at 125 oC, 20 min of extraction time, 0.08 of ginger to solvent ratio and 9 min of aging time of extraction parameters. The surface modeling was validated by plotting the observed and predicted value of zingiberene content and evidenced by the value of R-square at 0.76.